«GOLD SEPTEMBER», 1939 IN FOLK-LORE TRANSFORMATION - Kyrchiv, R. F. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
In the article an attempt is made to reveal the folklore transformation of “Golden September” of 1939. The author proves the authenticity of folk art in various songs, legends, proverbs and more.